A double‐blind, placebo‐controlled phase II study of the efficacy and safety of 2, 2‐dimethylbutyrate (HQK‐1001), an oral fetal globin inducer, in sickle cell disease. Issue 7 (15th April 2014) - Reid, Marvin E.; El Beshlawy, Amal; Inati, Adlette; Kutlar, Abdullah; Abboud, Miguel R.; Haynes, Johnson; Ward, Richard; Sharon, Bruce; Taher, Ali T.; Smith, Wally; Manwani, Deepa; Ghalie, Richard G.
<x xml:space="preserve">Abstract</x> This placebo‐controlled phase II study evaluated the pharmacodynamics, efficacy and safety of 2, 2‐dimethylbutyrate (HQK‐1001), a fetal globin gene‐inducing short‐chain fatty acid derivative, administered orally at 15 mg/kg twice daily for 48 weeks in 76 subjects with sickle cell disease (SCD). The median age was 26 years (range: 12–55 years) and 37 subjects (49%) were treated previously with hydroxycarbamide. Sixty subjects (79%) had Hb SS and 16 (21%) had S/β0 thalassemia. The study was terminated after a planned interim analysis showed no significant increase in fetal hemoglobin (Hb F) and a trend for more pain crises in the HQK‐1001 group. For 54 subjects with Week 24 data, the mean absolute increase in Hb F was 0.9% (95% confidence interval (CI): 0.1–1.6%) with HQK‐1001 and 0.2% (95% CI: −0.7–1.1%) with placebo. Absolute increases in Hb F greater than 3% were noted in 9 of 38 subjects (24%) administered HQK‐1001 and 1 of 38 subjects (3%) administered placebo. The mean changes in hemoglobin at Week 24 were comparable between the two groups. The mean annualized rate of pain crises was 3.5 with HQK‐1001 and 1.7 with placebo. The most common adverse events in the HQK‐1001 group, usually graded as mild or moderate, consisted of nausea, headache, vomiting, abdominal pain, and fatigue. Additional studies of HQK‐1001 at this dose and schedule are not recommended in SCD. Intermittent HQK‐1001 administration, rather than a daily regimen, may be better tolerated and more effective, as shown previously with arginine butyrate, and warrants further evaluation. Am. J. Hematol. 89:709–713, 2014. © 2014 Wiley Periodicals, Inc.